Avaliação in vitro e in vivo da eficácia de desinfetantes contra Trypanosoma vivax - Couto, Luiz Fellipe Monteiro (2019)
The present study aimed to evaluate the in vitro and in vivo efficacy of different disinfectants against Trypanosoma vivax. In the in vitro phase, 21 disinfectant solutions were tested in quintuplicate. Disinfectants added to micro tubes containing blood with approximately 1x106(1.000.000) trypomastigotes of T. vivax were evaluated at the 30 seconds, one minute, 10, 15 and 30 minutes of homogenization. After the feasibility evaluation from the thick drop technique, the mobile trypomastigotes were quantified for the calculation of efficacy. In the in vivo step, only disinfectants that demonstrated 100% efficacy and easy acquisition in vitro against the protozoan in question were used. To that end, 30 calves, crossbreed, three to six months old, negative for T. vivax (thick drop, Woo and cPCR) were divided into six different groups of five animals each, which were then inoculated with 46% and 70% alcohol disinfectant solutions or iodine 0.5% + 1x106 trypomastigotes of the protozoan in question at the time of 30 seconds or 1 minute of preparation. One group of animals was inoculated with only 1x106 T. vivax trypomastigotes (positive control), while another group of cattle were not infected (negative control). In order to diagnose the possible presence of T. vivax in the blood stream of the calves, on the 7th, 14th and 21st day after inoculation (DPI), blood was collected from each animal to investigate the protozoan by the techniques of Woo, Brener and cPCR. Based on the results, it can be concluded that in the in vitro stage, 13 of the 21 disinfectant solutions tested demonstrated 100% efficacy against T. vivax at all times of evaluation. Among these 13, alcohol 46%, alcohol 70% and iodine 0.5% were selected for in vivo stage. When the efficiency of these three disinfectants was evaluated in vivo, it was possible to verify that 60% and 20%, respectively, became infected by the protozoan in question, when inoculated with the total solution containing alcohol 46% + 1x106 trypomastigotes of T. vivax, after of 30 seconds and 1 minute of disinfection process. These results highlight the importance of performing the in vivo step in cattle when evaluating the immediate efficacy of disinfectants against T. vivax.